INTERNATIONAL LEGAL ASSISTANCE IN CRIMINAL MATTERS VS DIGITALIZATION OF CRIMINAL PROCEDURE: ARE THE CONCEPTIONS COMPATIBLE IN THE CONTEXT OF THE NEW US LEGISLATION? - Golovko, Leonid (State and Law, 2021)
The idea of digitalization of criminal procedure, turned into one of the ideological «markers» of the contemporary development, directly raises the question concerning the international cooperation of the states in criminal matters, essentially through the prism of the collection by one state of the evidence located on the territory of another state. The problem became even more complex after the adoption by the US of the Clarifying Lawful Overseas Use of Data Act (Cloud Act) 2018. There is an evident menace for the traditional approaches to mechanisms of the international legal assistance in criminal matters, based on principles of the state sovereignty and mutual respect of the states. This problem is underestimated in legal doctrine.